Healthy universities: betting on an integral student formation - Becerra Heraud, Silvia (2013)
This paper presents the proposal of healthy universities as an approach to health promotion feasible and necessary to work in higher education institutions. It exposes its definition and basic features, the steps to facilitate proper implementation and a historical review about the existing projects in universities of America and Europe. In Peru, there are several initiatives,among which the work of the Consortium of Universities and currently the start of thePUCP Healthy Program at the Pontifical Catholic University of Peru. Finally, it is done abrief review of the work implemented to date by this program.